The Effectiveness of Traffic Accident Compensation Claim Services PT. Jasa Raharja (PERSERO) - Aliya Rivani Putri; Siti Khumayah (Green Publisher Indonesia, 2026)
PT Jasa Raharja (Persero) is a state-owned company operating in the insurance sector under the supervision of the Ministry of Finance of the Republic of Indonesia. This company has a significant function in distributing compensation to victims who have experienced accidents. This study aims to assess the effectiveness of the compensation claim service provided by PT Jasa Raharja (Persero) in delivering traffic accident protection to the public. The study focuses on three indicators of effectiveness based on Duncan's theory in Steers (1985): goal achievement, integrity, and adaptation. The methodological approach is qualitative and descriptive in nature. Data sources consist of primary and secondary data, with data collection methods including observation, interviews, and documentation encompassing photographs. The results of the study show that the accident compensation claim process carried out by PT Jasa Raharja Cirebon City has been conducted in a manner consistent with established procedures; however, in practice, obstacles remain, including inconsistency in claim settlement times, limited public understanding of the role of PT Jasa Raharja (Persero), and a limited number of employees. These conditions indicate the need to increase the number of employees, strengthen comprehensive socialization efforts, and optimize the service process to operate more effectively